METODE IJTIHAD DAN KARAKTERISTIK FIQIH ABU HANIFAH - Abdurrahman Kasdi (Program Studi Hukum Keluarga Islam, 2014)
Fiqh compiled by Imam Abu Hanifa is clear and genuine about social equality. Imam Abu Hanifa was known as a Ra’yi scholar. Although he stayed in Mecca and learned hadiths, as well as other sciences from the characters he encountered, but the experience he gained from around Kufa enriching his collection of Hadith, and his methodology of fiqh reflects the school of Ahli Ra’yi that he learned. If he did not find explicit provision of legal issues from the Qur’an and Sunnah, he explored it from the words of the Companions in the form of ijma ‘or fatwa. If all three did not stated explicitly about the issues, then he searched through qiyas and istihsan, or looked at the traditions that developed in the community. He used ijtihad and reason, as well as how to use reason to compare opinions and to choose the most powerful opinion.Keywords: Fiqih, Ijtihad, Ahli Ra’yi, Madzhab